The tale of Mrs. Tittlemouse and other mouse stories - Potter, Beatrix (F. Warne & Co. England)
Contents: The tale of Mrs. Tittlemouse; The tale of Johnny Town-Mouse; The tale od two bad mice; The tailor of Gloucester